2022
DOI: 10.3389/fpsyg.2022.854065
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Support for Mental Health Workers Who Are Parents: A Feasibility Study

Abstract: BackgroundMental health workers are subject to high levels of occupational stress which is associated with poorer health and wellbeing and impaired patient outcomes. For individuals operating in high stress environments, reducing challenge at home, in particular around parenting, has been found to generalize into improvements in the professional domain. The present study sought to investigate the effectiveness and feasibility of brief targeted workplace intervention to support workers in terms of their parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As such, it combines components that are present within many community-delivered parenting interventions, with new components designed for a) parents who experience mental health difficulties and b) parents who specifically experience anxiety. In a randomised controlled trial (RCT), 16% fewer anxiety symptoms were reported in children whose parents were randomised to receive the course, compared to a control group ( 12 )a large (N>1800) national RCT ( 13 , 14 ) Furthermore, the research team has a track record in effectively adapting the RCC course for other contexts – it has been used by them as the foundation for an intervention designed to support NHS mental health workers who were parents ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…As such, it combines components that are present within many community-delivered parenting interventions, with new components designed for a) parents who experience mental health difficulties and b) parents who specifically experience anxiety. In a randomised controlled trial (RCT), 16% fewer anxiety symptoms were reported in children whose parents were randomised to receive the course, compared to a control group ( 12 )a large (N>1800) national RCT ( 13 , 14 ) Furthermore, the research team has a track record in effectively adapting the RCC course for other contexts – it has been used by them as the foundation for an intervention designed to support NHS mental health workers who were parents ( 15 ).…”
Section: Methodsmentioning
confidence: 99%